The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1159/000357556
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis as a Risk Factor for Retinopathy of Prematurity: A Systematic Review and Meta-Analysis

Abstract: Background: The role of chorioamnionitis (CA) in the development of retinopathy of prematurity (ROP) has not been well established. Objective: To conduct a systematic review and meta-analysis of the association between CA and ROP in preterm infants. Data Sources: The authors searched MEDLINE, Embase, CINAHL, Cochrane Central Register of Controlled Trials and PubMed, reviewed reference lists of relevant articles, abstracts and conference proceedings (Society for Pediatric Research, European Society for Paediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 138 publications
3
64
1
2
Order By: Relevance
“…Previous meta-analyses on the relationship between CA and BPD10, cerebral palsy6, or ROP13 showed that the positive association observed with unadjusted data was significantly reduced, or became non-significant, when adjusted data were pooled. The differences that we observed herein are even more marked since the significant positive association between CA and PDA became a significant negative association when only adjusted data were taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta-analyses on the relationship between CA and BPD10, cerebral palsy6, or ROP13 showed that the positive association observed with unadjusted data was significantly reduced, or became non-significant, when adjusted data were pooled. The differences that we observed herein are even more marked since the significant positive association between CA and PDA became a significant negative association when only adjusted data were taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CA may induce a fetal inflammatory response which is thought to play an important role in short- and long-term morbidity after very preterm birth12345678910111213. In recent years, numerous observational studies have been summarized in several meta-analyses attempting to clarify the association between CA and neonatal brain injury11, cerebral palsy6, bronchopulmonary dysplasia (BPD)710, necrotizing enterocolitis (NEC)12, and retinopathy of prematurity (ROP)13, among other adverse outcomes of prematurity. Nevertheless, since CA is a major risk factor for spontaneous preterm birth, the GA-independent contribution of CA to mortality and morbidity of preterm infants is very difficult to assess3.…”
mentioning
confidence: 99%
“…Higher rates of ROP have been demonstrated in infants born to mothers with histological and clinical chorioamnionitis relative to mothers without chorioamnionitis [54,55]. Chorioamnionitis and the accompanying fetal inflammatory response syndrome may increase the risk of ROP by directly sensitizing the developing retina to oxygen-induced changes in VEGF availability and subsequent vascular development and/or by causing systemic hypotension resulting in retinal hypoperfusion/ischemia [37,56]. These clinical data indicate a need for experimental studies to elucidate the pathophysiological mechanisms underlying the increased risk of ROP in infants exposed to chorioamnionitis [56].…”
Section: Retinal Vascular Development and Pathogenesis Of Retinopathymentioning
confidence: 99%
“…Chorioamnionitis and the accompanying fetal inflammatory response syndrome may increase the risk of ROP by directly sensitizing the developing retina to oxygen-induced changes in VEGF availability and subsequent vascular development and/or by causing systemic hypotension resulting in retinal hypoperfusion/ischemia [37,56]. These clinical data indicate a need for experimental studies to elucidate the pathophysiological mechanisms underlying the increased risk of ROP in infants exposed to chorioamnionitis [56]. Although the role of inflammation in ROP has been poorly investigated, some evidence in humans points to its contribution in ROP.…”
Section: Retinal Vascular Development and Pathogenesis Of Retinopathymentioning
confidence: 99%
“…Retrospective studies must consider this relationship when evaluating the association with morbidity, as preterm delivery itself is an independent risk factor for many of the morbidities that are associated with chorioamnionitis, and without careful analysis can overestimate the association of chorioamnionitis with various morbidities 33,34 . A result of this relationship between chorioamnionitis and preterm delivery is a synergistic exacerbation of neonatal morbidity, further incentivizing the importance of diagnosis and treatment of chorioamnionitis 55 .…”
Section: Complications and Concernsmentioning
confidence: 99%